(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
Even in ancient cultures, temporal experience was represented and narrated in different ways. For centuries, time travel has captured the human imagination. Although the first modern story dates back to 1733, it was probably only with the publication of The Time Machine by Herbert G. Wells in 1895 that this subject became a popular theme, used as a main or background topic in literature and film, and later in tv series, comics, video games. Even in scientific papers, it quickly became a hotly debated topic. In short, for more than 100 years, time travel has continued to capture the public imagination and has become a mass topic. This paper uses desk research methodology, narratological and mediological approach to analyze about 1,500 fictional works on time travel. The analysis suggests a categorization of the works into different types of plots based on the prevailing movement through time, such as journeys into the future, into the past, anywhere and time loops. The study reveals that around 60% of the stories involve journeys into the past, with motives ranging from exploratory expeditions with a tourist or educational perspective to journeys aimed at solving personal or collective problems. The conclusion proposes hypotheses as to why time travel remains a popular topic in today’s imagination, and why this distinct predilection for backward movement emerges. It explores the potential relationship between the difficulty of imagining the future and society’s perception of the social contract, particularly during a time in history when trust in societal institutions is increasingly in question.